Do firms R&D collaborations with the science system and enterprise group partners stimulate their product and process innovations? - S. A. Odei; Jan Stejskal (Economies, 2019)
There is a growing consensus that knowledge drives firms' process and product innovations. An important source of these innovations is from firms networking with R&D partners, such as those in the science system and other industries in the enterprise group. This paper aimed to examine firms' innovation collaborations with science systems and enterprise group partners and how these influence their product and process innovations. We focused on firms in the manufacturing sectors in the Czech Republic and Hungary. For our empirical analysis, we used the truncated data from the Eurostat Community Innovation Survey (CIS) 2012-2014, and the binary logistic regression model. Our results have demonstrated that firms' collaborations with these actors have a discernible positive influence on their product innovations. Conversely, the collaborations with these R&D partners for process innovations produced mixed results for both countries.
Keywords: L60; O30; O31; O52; 330; science system; knowledge; process innovations; product innovations; collaborations; Czech Republic; Hungary; Horizon 2020